PELATIHAN PEMBUATAN JAMU ALA CAFÉ BAGI IBU-IBU DAN PEMUDA DI DESA KERTAGENA TENGAH GUNA MENINGKATKAN PENDAPATAN RUMAH TANGGA - Askur Rahman; Hamzah Fansuri; Norita Vibriyanto; Yufita Listiana; Pia Amilia; Dinul Fadilah; Jumhadi Saifuddin; Dwi Wahyu; Achmad Riky Pratama (Jurnal Abdi Insani, 2026)
Jamu (traditional herbal medicine) is an integral part of Indonesia’s cultural heritage, widely recognized as a traditional remedy for maintaining health and treating various ailments. Traditional jamu has a bitter taste, an unpleasant aroma, and an unappealing appearance to younger generations. As a result, interest in jamu has been declining. Currently, the younger generation is highly interested in innovation and technology. Therefore, to maintain its relevance, modifications to jamu are necessary. A jamu-making training program conducted for youth aims to change the younger generation’s perspective that jamu does not always have a bitter taste and a pungent aroma. This activity is designed so that youth can create jamu that they can enjoy themselves and that can also serve as a business opportunity. This community service project was carried out in Kertagena Tengah Village over a three-month period, from September to November 2025, with activity locations determined by visiting each school directly. The target audience for the activities was housewives and young people. Based on the data collected, it can be concluded that the outreach and training activities on café-style herbal medicine were effective in increasing participants’ knowledge levels and expanding the target market. Knowledge improvement occurred across all measured aspects, with the most significant increase in understanding of herbal medicine raw materials, Turmeric Squash, and the concept of café-style herbal medicine. Overall, this activity succeeded in strengthening understanding and fostering a positive perception of café-style herbal medicine as an innovation rooted in local wisdom with a modern approach